The positive impacts of landscape fragmentation on the diversification of agricultural production in Zhejiang Province, China. (1st April 2020) - Qiu, Lefeng; Zhu, Jinxia; Pan, Yi; Wu, Shaohua; Dang, Yunxiao; Xu, Baogen; Yang, Hong
Abstract: Agricultural land fragmentation has an important impact on ecosystem services, especially food production. However, the relationship between land fragmentation and production diversification remains controversial and requires further analysis. This study characterized the dynamics of land fragmentation and production diversification in Zhejiang Province, China, from 1995 to 2015 using remote sensing, landscape metrics, and a diversification assessment approach. The results showed that Zhejiang Province experienced increasing fragmentation of agricultural landscapes and profound diversification of agricultural production. Fragmentation had a significant negative effect on grain crop production, but it had a significant positive effect on production diversification. These findings showed that fragmentation is an important driver of the diversification of agriculture and contributes to increased dietary diversity in local households. Therefore, we believe that when addressing land fragmentation issues, both the positive and negative impacts of fragmentation in different local conditions and circumstances should be taken into account. Our findings will provide scientific support for land consolidation management and agricultural land resource protection.